Menanamkan Pendidikan Karakter Peduli Lingkungan Melalui Gerakan Bring Your Tumbler Goes To School - Nurwahdah Nurwahdah; Citra Sepyusi Ikhsani (Universitas Negeri Padang, 2023)
Indonesia became a plastic waste emergency country, conveyed by Deputy IV of the Coordinating Ministry for Maritime Affairs and the Director General of Waste, Waste and Toxic Materials Management of Self-Defense (PSLB3) of the Ministry of Environment and Forestry in Kominfo.go.id. More than 100,000 animals per year die from plastic waste. The problem of plastic waste in the open environment should be everyone's concern because it has a significant impact on environmental change. School education patterns move and develop in accordance with the development of science and technology which not only teaches cognitive aspects (knowledge) but also affective aspects (attitudes) and psychomotor aspects (behavior / habits). With regard to affective attitudes, the government has established character education. One of the characters developed is to care for the environment. The character of caring for the environment is oriented to preserve the environment in everyday life by showing concern by preventing damage and acting continuously in an effort to repair the damage that has been done to nature and the environment. This research was written with a qualitative descriptive type of writing. Data collection techniques used literature review techniques. Data analysis was carried out by comparing the quintessence of the reading source. The implementation of environmental character education is to provide habituation to be able to reduce the use of plastic waste in schools with the Bring Your Tumbler Goes to School movement.